2022
DOI: 10.1101/2022.07.07.22277367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 in non-hospitalised adults caused by either SARS-CoV-2 sub-variants Omicron BA.1, BA.2, BA.5 or Delta associates with similar illness duration, symptom severity and viral kinetics, irrespective of vaccination history

Abstract: Introduction The impact of COVID-19 vaccination on disease in the community has been limited, as a result of both SARS-CoV-2 Variants of Concern that partially escape vaccine-induced immunity. We sought to characterise symptoms and viral loads over the course of COVID-19 infection in otherwise-healthy vaccinated adults, representative of the general population, to assess whether current self-isolation guidance remains justified. Methods In a prospective, observational cohort study, healthy vaccinated UK adult… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
2
10
0
Order By: Relevance
“…17 Previous studies have shown SARS-CoV-2 to be infectious up to 7-10 days following reporting of symptoms, and that infectiousness rarely continues more than 10 days. 26,27 This is reflected in our findings with IRRs attenuated towards the null in the 8-14 days following household infection, but the evidence for an increased IRR in this period compared with baseline is still pronounced, and may be consistent with some delay from testing and reporting. 28,29…”
Section: Discussionsupporting
confidence: 54%
“…17 Previous studies have shown SARS-CoV-2 to be infectious up to 7-10 days following reporting of symptoms, and that infectiousness rarely continues more than 10 days. 26,27 This is reflected in our findings with IRRs attenuated towards the null in the 8-14 days following household infection, but the evidence for an increased IRR in this period compared with baseline is still pronounced, and may be consistent with some delay from testing and reporting. 28,29…”
Section: Discussionsupporting
confidence: 54%
“…Measurement bias from self-reported symptoms may have occurred from recall error and viral variant differences among participants. Differences in viral load may have had an effect on the day of symptom onset in participants relative to initial infection, as variant-specific changes in symptom outcomes have been reported [44]. Furthermore, unvaccinated individuals in our analysis were mostly enrolled prior to the emergence and global spread of the Delta lineage, whereas fully vaccinated individuals were almost exclusively enrolled once Delta was the dominant circulating lineage.…”
Section: Plos Pathogensmentioning
confidence: 91%
“…The UCLH-Crick Legacy study (NCT04750356) is a prospective observational cohort, established in January 2021 to investigate longitudinal immunity to SARS-CoV-2. Extensive descriptions of the cohort can be found in our prior reports 7-10,14,15,25 . In the UK, from September 2023, healthcare workers, adults over 65 years, and those with either immunocompromised or caring responsibilities were offered a dose of COVID-19 vaccine as a 5 th dose booster.…”
Section: Methodsmentioning
confidence: 99%
“…The UCLH-Crick Legacy study (NCT04750356) is a prospective observational cohort, established in January 2021 to investigate longitudinal immunity to SARS-CoV-2. Extensive descriptions of the cohort can be found in our prior reports [7][8][9][10]14,15,25 Legacy participants were included in this study if they received their fifth dose of COVID-19 vaccine (BNT162b2+BA4/5 or BNT162b2-XBB.1.5) after August 1st 2023 and had a preboost sample taken more than 2 weeks after a previous dose and/or a post-boost sample within 4 weeks of a fifth dose 7 . We also analysed a subset of participants who contributed paired pre-and post-vaccination serum samples 7 .…”
Section: Clinical Cohortmentioning
confidence: 99%
See 1 more Smart Citation